(untitled) (American Journal of Islam and Society, 2010)
Yudi Latif’s Indonesian Muslim Intelligentsia and Power provides a broad, interdisciplinary, and long-term study of Indonesia’s Muslim intelligentsia from the late nineteenth until the early twenty-first century. His methodology stresses the reinterpretation of secondary sources, but does include primary data collected via a documentary and database survey, interviews, a questionnaire, and direct observation. Latif attempts to situate his multigenerational description and analysis within an interdisciplinary framework that includes politics, economics, education, discursive practices, the public sphere, and intellectual traditions. The book consists of seven chapters, including an introduction and a conclusion ...